Phytochemical screening and neuro-pharmacological activity of Mimosa pudica flowers: Integrating in vitro, in silico and in vivo approaches - Fahmida Alam; Rashedul Alam; A.T.M. Yusuf; Joya Datta Ripa; Raktim Das Nithin; Sourav Barua; Mohammed Fazlul Kabir; Seong-Tshool Hong; Hea-Jong Chung (Heliyon)
Throughout millennia, medicinal plants have been crucial in preserving human well-being and enhancing the whole human experience.Mimosa pudica, sometimes referred to as the ''sensitive plant,'' possesses considerable promise in the discovery of innovative herbal remedies. The objective of our research is to examine the various pharmacological uses of this mysterious plant by undertaking a thorough investigation of its methanolic extract. We employed sophisticated laboratory techniques to carefully extract and examine the chemical constituents of M. pudica. This examination uncovered a wide range of advantageous phytochemicals, such as alkaloids, flavonoids, tannins, and saponins. In order to evaluate the neuro-pharmacological effects of the extract, we conducted a comprehensive set of neurobehavioral tests on Swiss Albino mice. These tests included the open field test, light-dark box test, elevated plus maze test, tail suspension test, forced swim test, Y-maze test, hole cross test, and social interaction test. The extract, given at doses of 200 mg/kg and 400 mg/kg body weight, showed notable effects on neurobehavioral parameters, similar to the conventional medications Diazepam and Escitalopram (1 mg/kg body weight). In addition, we conducted in-silico activities on hMAO A and hMAO B receptors by performing molecular docking studies on 11 compounds that were identified using GC-MS analysis. The results of our investigation revealed the chemical properties of M. pudica and emphasized its potential as a substance that can reduce anxiety and depression. It also has effects on memory and learning, which could lead to significant gains in pharmaceutical development and medical progress.